Inovasi dalam Pendidikan di Madrasah Tsanawiyah: Membangun Keterampilan Berbahasa Inggris yang Efektif melalui Program “Two Phrases to Grow” - Muliana Setia Hapsari; Hesty Widiastuty (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service program addresses challenges in mastering basic English vocabulary due to limited learning time, minimal exposure to English, and a lack of varied teaching methods. The